Parameter estimation of soil water retention curve with Rao-1 algorithm - Zhongju Wang; Chao Huang; Long Wang (Journal of Agricultural Engineering, 2022)
The soil water retention curve (SWRC) has a significant role in determining the unsaturated properties of soil. A stochastic optimization algorithm named Rao-1 algorithm is employed to estimate the parameters of the SWRC model in this paper. The Rao-1 algorithm is a simple heuristic search algorithm containing only addition and multiplication operations. This paper introduces the method and its application in the determination of soil water retention model parameters in detail. In this study, van Genuchten model is used to depict the SWRC for its good fitting capacity, and parameters of the van Genuchten model are determined using Rao-1 algorithm. The feasibility and efficiency of the method are validated via the experimental results of 24 soil samples of 12 soil textural classes. Besides, the performance of Rao-1 algorithm is compared with that of Particle Swarm Optimization algorithm, Differential Evolution algorithm, and RETC program. Through comparative analysis, Rao-1 algorithm outperforms other methods in determining SWRC parameters.